Progress on the Sustainable Development Goals: The Gender Snapshot 2021 - United Nations Women (United Nations, 2021)
A year and a half into the pandemic, progress towards expanding women’s rights and opportunities continues to be tested and impeded. Women’s economic losses have not rebounded, hunger is on the rise, and school closures threaten to destroy girl’s educational gains. Women’s participation in government, research and resource management remains far from equal. Vulnerable groups of women - including migrants, those with disabilities and those affected by conflict – are too frequently left out and left behind and disparities between rich and poor countries are preventing equal access to lifesaving COVID-19 vaccines and treatments. But swift action and targeted interventions can halt the decline and drive forward equal rights for women and girls. The 2021 Gender Snapshot: Progress towards the Sustainable Development Goals brings together the latest evidence on gender equality across all 17 Sustainable Development Goals, taking stock of the progress achieved and the challenges that remain.